Laparoscopic Versus Abdominal Approach to Endometrial Cancer: A 10-Year Retrospective Multicenter Analysis. Issue 3 (1st March 2012) - Palomba, Stefano; Ghezzi, Fabio; Falbo, Angela; Mandato, Vincenzo Dario; Annunziata, Gianluca; Lucia, Emilio; Cromi, Antonella; Abrate, Martino; La Sala, Giovanni Battista; Giorda, Giorgio; Zullo, Fulvio; Franchi, Massimo
Abstract : Objective: The objective of this study was to give a reality-based picture of the use of laparoscopic surgery for staging endometrial cancer patients out of the experimental setting. Methods: Consecutive data of patients with endometrial cancer who underwent laparoscopic or abdominal surgical staging in 6 Italian centers were recorded. Baseline patients and tumors characteristics, surgery performed, and safety data were collected and analyzed. Results: A total of 1012 subjects (403 and 609 treated by laparoscopy and laparotomy, respectively) who received surgical stadiation for endometrial cancer were included in the final analysis. The laparoscopic approach to endometrial cancer was more commonly performed in younger and nonobese patients who had received less previous surgeries, whereas the abdominal approach was preferred for the advanced stages and rare histotypes. Irrespectively to stage, the operative time was higher for the laparoscopy than laparotomy, whereas blood loss and postoperative complications were lower in the laparoscopy group than in the laparotomy group. No difference between surgical approaches was observed in complication rates in stage I endometrial cancers, whereas they were worst in higher stages. The site, but not the incidence, of recurrences differed only for advanced stage endometrial cancers. No differences in overall, disease-free, and cancer-related survival rates were also observed. Conclusions: In the clinical practice, heterogeneous criteria are adopted to recur to laparoscopy for staging endometrial cancer. The safety and the feasibility of the laparoscopy are confirmed for stage I endometrial cancers, whereas they appear suboptimal for the advanced stages.